Fabrication of a sensitive electrochemical sensor based on modified carbon paste electrode for hydrazine analysis in water samples - Ahmad Amer Al-Salman; Rafah Mohammed Thyab; Muhammad Abdel Hasan Shallal (Journal of Electrochemical Science and Engineering, 2025)
A new electrochemical sensor based on a CuS-modified carbon paste electrode (CPE) was fabricated for the determination of hydrazine. In comparison with the bare CPE, the The CuS-modified electrode significantly enhanced the electrooxidation performance of hydrazine by reducing the oxidation overpotential and increasing the oxidation peak current. Differential pulse voltammetry was used as the analytical method for the quantitative determination of hydrazine. The anode peak current was linearly related to hydrazine concentrations between 0.06 and 270.0 μM with a detection limit of as little as 0.02 μM. The sensor modification also showed good stability, reproducibility, and sensitivity. In addition, experimental results demonstrated the reliability and effectiveness of the sensor in determining hydrazine in various types of water samples.